Chimpanzee integration: assessment of affiliative/aggressive behaviors between two captive groups - Vicente, Sara Andreia Oliveira (2022)
Animal welfare is an increasingly debated topic, concerning both scientists and common citizens. Nevertheless, many exotic specimens are still kept in captivity for various reasons and basic welfare standards are not always met. Some organizations work on rescuing individuals of such situations and providing them with appropriate care. For rescued individuals, group formation and management can provide a new opportunity to establish relationships with conspecifics and to develop species-specific behaviors. These procedures can also be dangerous and so careful planning is necessary as to minimize the risks. In this study, the interactions between captive chimpanzees of two social groups housed contiguously were assessed in order to evaluate the possibility of uniting all individuals into a single social group. Prior to the start of this study, all individuals were already familiar with each other and had the opportunity to interact daily. Results show the prevalence of affiliative behaviors and the inexistence of agonistic interactions between all individuals and so it was determined that the introductory procedure could take place. The behaviors of the initial contact corresponded to those observed in similar situations and were indicative of an overall successful integration, with the chimpanzees returning to normal behaviors on the three days after this event. It is expected that the individuals maintain a stable social dynamic over time, with an increase on the number of interactions between them, leading to a greater welfare level. Additionally, the influence of social media on the acquisition of exotic pets is discussed.